The Impact Of Product Knowledge And Brand Image On Purchasing Decisions Through Word Of Mouth At Imural - Winadi Prasetyoning Tyas, Ari Anggarani; Elvira, Rani (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2024)
This study examines the impact of product knowledge and brand image on purchasing decisions through word of mouth at IMURAL, a commercial art company specializing in murals. The research focuses on consumers who use IMURAL's services and professionals in the field of interiors and architecture in South Jakarta. The study addresses the lack of public awareness about murals, the negative perception of murals as vandalism, and the limited promotional media for IMURAL. The sample consists of 150 respondents selected through purposive sampling. The Structural Equation Model (SEM) and Partial Least Square (PLS) analysis are used to assess the relationships between variables. The findings suggest that brand image significantly influences purchasing decisions, while product knowledge does not. Additionally, word of mouth significantly affects purchasing decisions, and both product knowledge and brand image indirectly impact purchasing decisions through word of mouth. These findings highlight the importance of brand image and word of mouth in shaping consumers' purchasing decisions and emphasize the potential of murals as a form of interesting and personalized art.